The FONT4 ILC intra-train beam-based digital feedback system prototype - Burrows, P; Christian, G; Clarke, C; Constance, B; Khah, H; Hartin, T; Perry, C; Swinson, C; Kalinin, A; Molloy, S; White, G; IEEE (2007)
We present the design of the FONT4 intra.-train beam-based digital position feedback system prototype. The system incorporates a fast analogue beam position monitor front-end signal processor, a digital feedback board, and a fast kicker-driver amplifier. The system latency goal is less than 150ns. We report preliminary results of beam tests at the Accelerator Test Facility (ATF) at KEK using electron bunches separated by c. 150ns.